1968
DOI: 10.1126/science.159.3822.1493
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid: A New Name for Abscisin II (Dormin)

Abstract: Slatis has raised a single valid point. The chromosome-per-cell distributions displayed in our put numbers on our observations. We do recognize the implications of such damage in our experimental cell populations, if the observations were significantly elevated above control values. We cannot say that they were, or that they were not.We feel that Slatis' attempt to show chromosome damage by pointing to differences which are the result of random sampling error is not a matter of a one-tailed or a two-tailed tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 6 publications
0
34
0
2
Order By: Relevance
“…Later, an isolated compound from the leaves of birch and maple trees, now known as dormin, was revealed to trigger a resting state in the trees buds [53]. In 1967, abscisin and dormin were combined with the unique name of abscisic acid (ABA) [54]. Structural formula of ABA, a sesquiterpene (C15), is presented in Figure 2.…”
Section: Abscisic Acidmentioning
confidence: 99%
“…Later, an isolated compound from the leaves of birch and maple trees, now known as dormin, was revealed to trigger a resting state in the trees buds [53]. In 1967, abscisin and dormin were combined with the unique name of abscisic acid (ABA) [54]. Structural formula of ABA, a sesquiterpene (C15), is presented in Figure 2.…”
Section: Abscisic Acidmentioning
confidence: 99%
“…During this same period, Cornforth et al (1965) were successful in isolating a compound from sycamore leaves, denoted dormin, that proved to be involved in bud dormancy. A comparative analysis of the chemical structures of these two compounds by infrared spectroscopy revealed that they were one and the same compound (Addicott et al 1968) and, following its purification and determination of its chemical structure, this compound was renamed abscisic acid (ABA). Subsequent studies revealed that the ABA level increases considerably when plants wilt (Wright and Hiron 1969) and that ABA causes stomatal closure (Mittelheuser and Van Steveninck 1969).…”
Section: Introductionmentioning
confidence: 98%
“…ABA was discovered in the early 1960s by different groups studying abscission in cotton and lupine fruits, and bud dormancy in woody plants (Addicott et al 1968). Since then, the roles of ABA have become obvious in both physiological and adaptive responses of plants (Christmann et al 2006).…”
Section: Abscisic Acidmentioning
confidence: 99%